A view on the skin–bone axis: unraveling similarities and potential of crosstalk - Morimoto, Tadatsugu; Hirata, Hirohito; Sugita, Kazunari; Paholpak, Permsak; Kobayashi, Takaomi; Tanaka, Tatsuya; Kato, Kinshi; Tsukamoto, Masatsugu; Umeki, Shun; Toda, Yu; Mawatari, Masaaki (Frontiers in Medicine, 2024)
As the population ages and bone metabolic diseases continue to increase, a detailed understanding of skin-bone interactions is essential to address unmet clinical needs. The phrase "skin as a mirror of internal medicine", which means that the skin reflects many of the diseases of the internal organs, is a well-known notion. Despite the phenotypic differences between the soft skin and hard bone, the skin and bone are highly associated. Skin and bone consist of fibroblasts and osteoblasts, respectively, which secrete collagen and are involved in synthesis, while Langerhans cells and osteoclasts control turnover. Moreover, the quality and quantity of collagen in the skin and bone may be modified by aging, inflammation, estrogen, diabetes, and glucocorticoids. Skin and bone collagen are pathologically modified by aging, drugs, and metabolic diseases, such as diabetes. The structural similarities between the skin and bone and the crosstalk controlling their mutual pathological effects have led to the advocacy of the skin-bone axis. Thus, the skin may mirror the health of the bones and conversely, the condition of the skin may be reflected in the bones. From the perspective of the skinbone axis, the similarities between skin and bone anatomy, function, and pathology, as well as the crosstalk between the two, are discussed in this review. A thorough elucidation of the pathways governing the skin-bone axis crosstalk would enhance our understanding of disease pathophysiology, facilitating the development of new diagnostics and therapies for skin collagen-induced bone disease and of new osteoporosis diagnostics and therapies that enhance skin collagen to increase bone quality and density.